Nonlinear Optics Applications: in memory of George I. Stegeman - Assanto, Gaetano (Photonics Letters of Poland, 2016)
Last May 2015 Prof. George I. Stegeman suddenly passed away at the age of 72. With him, the community of nonlinear optics and, in particular, researchers working on guided-wave nonlinear optics, lost one of the most enthusiastic pioneers and scholars in the field. An insightful scientist, a creative thinker, a motivated researcher, a fantastic teacher, a careful supervisor, a generous man, an outstanding listener, a proud husband and father, George was also a party person, a football and basketball fan, a world traveler. He was loved by his students, collaborators and friends because was able to recognize and appreciate everybody?s qualities and talents, from science to sports, from cooking to playing, from story-telling to car-driving. In short, George Stegeman was a gracious man in spite of his prominent role of world-renowned scientist. Full Text: PDF References M.A. Karpierz, G.I. Stegeman, "Nonlinear Optics: A Vibrant Field", Photon. Lett. Poland 1, 145 (2009). CrossRef M.A. Karpierz, G. Assanto, "Nonlinear Optics Applications", Photon. Lett. Poland 4, 1 (2012). CrossRef G.I. Stegeman, R.A. Stegeman, Nonlinear Optics, Phenomena, Materials and Devices (John Wiley & Sons, Hoboken, New Jersey 2012).